2011
DOI: 10.3109/0284186x.2011.608084
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal lesions in patients with extra-adrenal malignancy – benign or malignant?

Abstract: An adrenal lesion occurring in a patient with past malignancy has a high likelihood of representing a benign lesion, and even in patients with present signs of malignant disease at least one fourth to one half of such lesions are benign. Dedicated adrenal imaging including computed tomography attenuation measurements with wash-out characteristics, in addition to biochemical testing for adrenal dysfunction, is highly recommended in these cases, especially in patients without any other signs of metastatic spread. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…A solitary adrenal mass is identified at the time of the cancer diagnosis or during follow‐up in many oncology patients. Similar to the results of our study, previous studies have shown that metachronous adrenal mass in patients with cancer more often metastasized than synchronous adrenal mass . Howell et al, in a study in which the largest proportion of primary cancers were of the lung (50%), reported that 51 of 61 patients with adrenal metastasis had metachronous mass .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A solitary adrenal mass is identified at the time of the cancer diagnosis or during follow‐up in many oncology patients. Similar to the results of our study, previous studies have shown that metachronous adrenal mass in patients with cancer more often metastasized than synchronous adrenal mass . Howell et al, in a study in which the largest proportion of primary cancers were of the lung (50%), reported that 51 of 61 patients with adrenal metastasis had metachronous mass .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the results of our study, previous studies have shown that metachronous adrenal mass in patients with cancer more often metastasized than synchronous adrenal mass. 2,5 Howell et al, in a study in which the largest proportion of primary cancers were of the lung (50%), reported that 51 of 61 patients with adrenal metastasis had metachronous mass. 23 In a study involving a large proportion of RCC cases (57%), Lenert et al showed that metachronous adrenal metastasis was more common than synchronous metastasis in patients with extra-adrenal malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study observed that an unenhanced CT attenuation value of ≥10 HU for an adrenal lesion is highly sensitive but poorly specific (31% -39%) for malignancy. The high sensitivity is in accordance with adrenalectomy histopathologic findings when correlated with imaging characteristics [38]. In order to improve specificity, recent studies recommend using cut-off values of 20 HU or 25 HU to achieve specificities of 60% or 72%, respecttively [9].…”
Section: Discussionsupporting
confidence: 54%
“…Although the risk of an adrenal malignancy is higher in patients with a history of malignancy, Hammarstedt et al demonstrated that up to 74 % of these lesions are still likely benign when assessed by imaging criteria and recommended long-term follow-up, especially when no other concurrent malignancy is radiographically evident. 4,21 Furthermore, the incidence of a solitary metastatic lesion to the adrenal was unusual (\10 %) in a recent review of our institutional data. 22 The practice at our institution is to evaluate unilateral adrenal lesions in patients who have a history of extra-adrenal malignancy with standard biochemical testing and imaging characterization and use indications for resection that do not necessarily differ from patients who do not have a personal history of cancer.…”
Section: Discussionmentioning
confidence: 95%